A Novel Symmetric Encryption Algorithm and its Implementation - Baykara, Muhammet; Daş, Resul; Tuna, Gürkan (Fırat University, 2017)
Confidentiality of digital data stored on computer systems or transmitted via computer networks is very important in the digital era and it can be addressed with a variety of solutions such as encryption. In this respect, in this study we propose a new encryption algorithm based on a number of mathematical terms, formulas and operations. The proposed algorithm is a general purpose symmetric encryption algorithm; hence, it can be used for various purposes. The proposed algorithm is implemented an application called Secure Text. Although the developed application encrypts text, the algorithm is suitable for encrypting several file types including .txt, .rtf, .doc, .docx, .xls, .xlsx, .ppt, .pptx, .pdf, .png, and .bmp. A set of evaluation study carried out using the developed application shows that although the proposed algorithm is simple and performs very quickly, it is complicated enough and robust against potential unorganized threats.

Bilgisayar sistemlerinde depolanan ya da bilgisayar ağları üzerinden iletilen dijital verilerin gizliliği günümüz dijital çağında oldukça önemlidir. Gizliliğin sağlanması için şifreleme gibi birçok çözüm yolu mevcuttur. Bu bağlamda, bu çalışmada bir dizi matematiksel terim, formül ve işlemlere dayalı yeni bir şifreleme algoritması önerilmiştir. Önerilen algoritma genel amaçlı simetrik bir şifreleme algoritması olduğundan çeşitli amaçlarla kullanılabilmektedir. Önerilen uygulama Secure Text adlı bir uygulama içerisinde kodlanmıştır. Geliştirilen uygulama, metinleri şifrelemesinin yanı sıra. txt, .rtf, .doc, .docx, .xls, .xlsx, .ppt, .pptx, .pdf, .png, ve bmp vb. birçok dosya tipindeki dosyaların da şifrelenmesi için kullanılabilmektedir. Önerilen uygulama üzerinde gerçekleştirilen bir dizi deneme testi sonucunda, önerilen algoritmanın basit, hızlı uygulanabilir olduğu ve özellikle olası kırma ataklarına karşı yeterince sağlam olduğu gözlenmiştir
Yeni Bir Simetrik Şifreleme Algoritması ve Uygulanması